Acute renal failure secondary to rosuvastatin-induced rhabdomyolysis - Mohammad , Mona; Khan, Owais (Indian Journal of Case Reports, 2025)
Rhabdomyolysis is a condition characterized by muscle necrosis and can range from asymptomatic elevation of serum muscle enzymes to life-threatening cases associated with extremely elevated enzyme levels, electrolyte imbalances, and acute renal failure (ARF). Here, we present the case of a 76-year-old woman who developed rhabdomyolysis and ARF secondary to an increase in her rosuvastatin from 10 to 40 mg. In this report, we present a case of a 76-year-old woman who presented with decreased appetite and reduced urine output, presumed to be due to a recent increase in her rosuvastatin dosage leading to rhabdomyolysis.